'Privations' as a Development Concern: A Study of Two Communities in the National Capital Region of India. (March 2020) - Vijay, Devesh
Development scholars are tracking a wide range of well-being indices across countries including life expectancy, school enrolment and a wide range of 'freedoms' now. Yet, a critical set of 'privations' or collective hardships, that undermine general well-being and call for concerted public response, still remain excluded from the mainstream development discourse. This article highlights six sets of major 'privations' relevant to development studies based on an extended fieldwork in a village and a slum on Delhi's periphery. It consists of four sections. The first section elucidates the conceptualisation of 'privations', its principal categories and their distinction from related terms such as deprivations, poverty and suffering. The next section explains the multi-method approach used in this study to track 'privations' in the studied communities (called Dhantala and Aradhaknagar) through surveys, interviews and group discussions conducted since 1988. The third segment of the article focuses on two specific 'privations', namely safety and health risks experienced by studied subjects over the recent decades. The article concludes with reflections on reasons for the neglect of the cited 'privations' in dominant development discourses. It offers suggestions for their better coverage in development indices and their mitigation by more concerted government response and civic action, in future.